1960
DOI: 10.1063/1.1731070
|View full text |Cite
|
Sign up to set email alerts
|

Excluded Volume Effect of Linear Polymer Molecules

Abstract: A new closed expression for the excluded volume effect of linear polymer molecules is developed with the aid of an equivalent ellipsoid model, in which the polymer chain with fixed ends is replaced by a uniform distribution of unconnected segments within an ellipsoid whose dimensions are chosen to give the correct principal radii of gyration of the chain. The linear expansion factor a for a chain of N segments is given bywhere a is the effective bond length and I'l is the binary cluster integral of a segment p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
1

Year Published

1966
1966
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 255 publications
(20 citation statements)
references
References 24 publications
0
19
0
1
Order By: Relevance
“…13 The investigation of the other extreme, i.e., the asymptotic solution for R at large z, has been initiated by Edwards'4, applying the self-consistent field method. Subsequently, this approach has been further investigated by Reiss'5 and others '6' 17 21 22 We note that integro-differential equations have also been derived by the liquid theory approach23 24 As for the derivation of approximate closed expressions for R or , various attempts have been made for many years3. In these the problem has been approached from two starting points.…”
Section: Expansion Factorsmentioning
confidence: 99%
“…13 The investigation of the other extreme, i.e., the asymptotic solution for R at large z, has been initiated by Edwards'4, applying the self-consistent field method. Subsequently, this approach has been further investigated by Reiss'5 and others '6' 17 21 22 We note that integro-differential equations have also been derived by the liquid theory approach23 24 As for the derivation of approximate closed expressions for R or , various attempts have been made for many years3. In these the problem has been approached from two starting points.…”
Section: Expansion Factorsmentioning
confidence: 99%
“…(6) vor : a2-1 = C.j(ii)ii bzw. a5-a3 = C.j(I)z, (8) wobei j(E) eine mit wachsendem z abfallende Funktion von ii und C = 134/105 ist *). Hier is t a* der thermische kubische Ausdehnungskoeffizient der Losung.…”
Section: (4) (5)unclassified
“…Moreover, they observed that at 500,000 d [700-800 base pairs (bp)] the double-stranded poly(A) and the DNA had measured relaxation times which were substantially below the value predicted for a rigid rod [~(observed)/~(rigid) = 0. 41 for DNA]. Although these studies were subject to the first two uncertainties mentioned above, they suggest an approach to the study of the flexibility of DNA which would be quite sensitive to small changes in overall configuration.…”
Section: Introductionmentioning
confidence: 99%